Monitoring of the Tolitoli Regency Bawaslu on Violations of the Neutrality of the State Civil Apparatus in the Implementation of the 2020 Regional Head Elections - Warda Said (Formosa Journal of Sustainable Research, 2023)
Neutrality is a principle that must be obeyed by all civil servants. However, several ASN’ in Tolitoli Regency were proven to have taken non-neutral actions towards pairs of Regional Head candidates in the 2020 Pilkada. The purpose of this study was to analyze how the monitoring of ASN neutrality in the Tolitoli Regency Pilkada resulted in violations. This study used empirical normative methods with qualitative descriptive analysis, namely studies laws that view law as principles, norms and their application in practice in society, produce descriptive data in the form of research notes or data found in the field. The results of the study revealed the lack of neutrality of ASN in Tolitoli Regency as evidenced by violations and facts on the ground, that violations of the principle of neutrality committed by ASN were due to weak sanctions achieved, there were still ASN’ who could not understand in detail the rules of neutrality regarding how to act neutrality. Perpetrators of violations are only subject to moral sanctions and are given administrative action in accordance with statutory regulations. In fact, this punishment did not make ASN afraid to commit violations and there were even ASN employees who received two KASN recommendations